CLINICAL SYMPTOMS AND THERAPEUTIC APPROACHES IN PATIENTS WITH GENERAL ANXIETY DISORDER - Dewa Gede Bagus Surya Parama Artha; Luh Putu Pranena Sastri, Ni; Purnomo, Ketut Indra (International Journal of Multidisciplinary Reseach, 2025)
Generalised Anxiety Disorder (GAD) is a psychological condition characterised by widespread, uncontrollable, and persistent anxiety in multiple domains, including work, health, and social contexts. Common symptoms include muscle tension, sleep disturbances, fatigue, impaired concentration, and excessive anxiety relative to circumstances. This condition can interfere with daily functioning and reduce an individual's quality of life. This study used a qualitative methodology using in-depth interviews with five psychiatric physicians to determine the main symptoms, etiological factors, and therapeutic strategies for Generalised Anxiety Disorder (GAD). This study revealed that all informants showed consistent patterns of physical and psychological symptoms. These factors include genetics, neurochemical imbalances, high-stress environments, and predisposed personality traits. Regarding treatment, physicians recommend implementing cognitive behavioural therapy, pharmaceutical interventions, relaxation and mindfulness practices, and adopting a healthy lifestyle in a coordinated manner. Generalised Anxiety Disorder is a multifaceted condition that requires a holistic approach. Appropriate and ongoing treatment can help individuals manage anxiety well and improve their quality of life. The findings of this study are expected to serve as a reference in clinical practice and the development of mental health interventions